2021
DOI: 10.1177/20427530211028067
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond four walls and forming a learning community for speaking practice under the auspices of Facebook

Abstract: There is a paucity of opportunities for Vietnamese EFL students to use and practise English speaking skills both inside and outside the classroom, attributing to students’ lack of interest and motivation in improving their speaking skills. Given that learning can be distributed across a multitude of formal and informal settings, the social and informal features of Facebook serve as potentially ubiquitous support for students to productively practise and use the target language. To date, however, much of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…This assessment comprises 30 statement pairs designed to reveal a respondent's conflict resolution style. This test suggests two scales: "assertiveness" and "cooperativeness", with the help of which five different conflict modes: competing (assertive, not collaborating), avoiding (unassertive, not collaborating), accommodating (unassertive, collaborating), collaborating (assertive, collaborating), and compromising (interim assertiveness, and readiness to collaboration), are registered (Duong & Pham, 2022). The validity of this test has been proven by its authors Thomas and Kilmann (1978).…”
Section: Methodsmentioning
confidence: 98%
“…This assessment comprises 30 statement pairs designed to reveal a respondent's conflict resolution style. This test suggests two scales: "assertiveness" and "cooperativeness", with the help of which five different conflict modes: competing (assertive, not collaborating), avoiding (unassertive, not collaborating), accommodating (unassertive, collaborating), collaborating (assertive, collaborating), and compromising (interim assertiveness, and readiness to collaboration), are registered (Duong & Pham, 2022). The validity of this test has been proven by its authors Thomas and Kilmann (1978).…”
Section: Methodsmentioning
confidence: 98%
“…Through the assistance of learning communities facilitated by social media platforms, students can engage in socio-cultural interactions and actively practice their oral English skills. This is made possible due to the easy accessibility, flexible schedules shared resources, and collaborative attributes of learning communities (Duong and Pham, 2022). In general, learning communities hold the potential to foster desire and motivation within online or distance learning contexts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These thirty articles revealed that there are five groups of targeted subjects that are of interest to researchers. A significant sum of studies was performed on the tertiary education level learners with 19 articles contributing to the list [30,31,35,36,[38][39][40]43,45,46,[48][49][50][51][52][53][54][55]58]. Five articles were directed towards the response from educators [33,34,42,56,57].…”
Section: N/a /mentioning
confidence: 99%
“…Based on Table 4 below, it can be deduced that Facebook has received the most attention as a single SNS platform to determine the efficacy of SNS in English language learning. Five articles [36,38,41,49,50] have researched the assimilation of Facebook in formal English learning whereas only one article [42] employed Facebook for informal English learning. About a third of the total articles reviewed [29,35,37,39,40,45,46,48,[51][52][53]57] have not specified any SNS platform in the research, indicating that a lot of studies were done to investigate the influence of SNS as a whole on learning rather than just a single platform.…”
Section: Rq 1: What Are the Types Of Social Networking Sites (Sns) Pl...mentioning
confidence: 99%